2020
DOI: 10.1186/s12864-020-6669-y
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation in human genomes from three major ethno-linguistic groups in Africa

Abstract: Background: Copy number variation is an important class of genomic variation that has been reported in 75% of the human genome. However, it is underreported in African populations. Copy number variants (CNVs) could have important impacts on disease susceptibility and environmental adaptation. To describe CNVs and their possible impacts in Africans, we sequenced genomes of 232 individuals from three major African ethno-linguistic groups: (1) Niger Congo A from Guinea and Côte d'Ivoire, (2) Niger Congo B from Ug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…24 An analysis of copy number variation has been published separately. 25 From the 1000 Genomes project 16 we obtained variant call files of 50 samples from each of the Esan and Yoruba from Nigeria; Mende from Sierra Leone; Gambian from Western Division of The Gambia; Luhya from Western Kenya; five samples from each of five populations of West Eurasian origin: Utah residents with northern and western European ancestry, Finnish from Finland, British in England and Scotland, Iberian from Spain, Toscani from Italy.…”
Section: Study Samplesmentioning
confidence: 99%
“…24 An analysis of copy number variation has been published separately. 25 From the 1000 Genomes project 16 we obtained variant call files of 50 samples from each of the Esan and Yoruba from Nigeria; Mende from Sierra Leone; Gambian from Western Division of The Gambia; Luhya from Western Kenya; five samples from each of five populations of West Eurasian origin: Utah residents with northern and western European ancestry, Finnish from Finland, British in England and Scotland, Iberian from Spain, Toscani from Italy.…”
Section: Study Samplesmentioning
confidence: 99%
“…Over the years, additional studies of individuals from diverse populations, including of African descent as part of 1000 Genomes Project, reported an increasing number of CNVs (> 50,000) [ 20 23 ]. Most recently, CNVs and other structural variants (> 400,000) in 4937 individuals of African and African American ancestry were reported as part of the Genome Aggregation Database (gnomAD) [ 29 , 43 ], and novel CNVRs were identified by Nyangiri and colleagues [ 44 ]. In our study, we identified 48 CNVRs which may represent CNVRs that are either specific to the Bantu African population or that may be very rare in populations currently represented in existing CNV datasets.…”
Section: Discussionmentioning
confidence: 99%
“…We compared Bantu CNVRs to variants obtained from DGV (release date 2020-02-15) [41], the Genome Aggregation Database (gnomAD v2.1) [29,43], African CNVR [44] and CNVs identified in low-mappability regions [45]. DGV CNVs dataset were downloaded from DGV website [46].…”
Section: Comparison To Other Cnv Datasetsmentioning
confidence: 99%
“…We compared Bantu CNVRs to variants obtained from DGV (release date 2020-02-15) (23), the Genome Aggregation Database (gnomAD v2.1) (21,24), African CNVR (25) and CNVs identified in low-mappability regions (26). DGV CNVs dataset were downloaded from DGV website (61).…”
Section: Comparison To Other Cnv Datasetsmentioning
confidence: 99%
“…Over the years, additional studies of individuals from diverse populations, including of African descent as part of 1000 Genomes Project, reported an increasing number of CNVs (>50000)(37)(38)(39)(40). Most recently, CNVs and other structural variants (> 400000) in 4937 individuals of African and African-American ancestry were reported as part of the Genome Aggregation Database (gnomAD)(21,24), and novel CNVRs were identified by Nyangiri and colleagues(25).…”
mentioning
confidence: 99%